2015
DOI: 10.1371/journal.pone.0130347
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Evolution of the Allatostatin-Type A, KISS and Galanin Peptide-Receptor Gene Families in Bilaterians: Insights from Anopheles Mosquitoes

Abstract: Allatostatin type A receptors (AST-ARs) are a group of G-protein coupled receptors activated by members of the FGL-amide (AST-A) peptide family that inhibit food intake and development in arthropods. Despite their physiological importance the evolution of the AST-A system is poorly described and relatively few receptors have been isolated and functionally characterised in insects. The present study provides a comprehensive analysis of the origin and comparative evolution of the AST-A system. To determine how e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 116 publications
1
50
1
Order By: Relevance
“…As our phylogenetic analysis confirms, Apime-ASTA-R and Apime-ASTC-R belong to two distinct receptor families that include, respectively, mammalian galanin and somatostatin receptors [ 19 , 50 , 96 98 ]. Yet, as is often the case for small neuropeptides, this conservation does not fully apply to the ligands.…”
Section: Discussionmentioning
confidence: 59%
“…As our phylogenetic analysis confirms, Apime-ASTA-R and Apime-ASTC-R belong to two distinct receptor families that include, respectively, mammalian galanin and somatostatin receptors [ 19 , 50 , 96 98 ]. Yet, as is often the case for small neuropeptides, this conservation does not fully apply to the ligands.…”
Section: Discussionmentioning
confidence: 59%
“…However, a comprehensive evolutionary study of the AstA receptor 1 gene revealed that it shares an evolutionary ancestor gene with the mammalian GPR54 receptor gene [41]. Moreover, the Drosophila AstA peptide and the human KISS peptide share a conserved FGL motif, suggesting that AstA and KISS could originate from a common ancestor [41]. As previously mentioned, the KISS/GPR54 pathway promotes pulsatile secretion of GnRH, a necessary event for steroid production and sexual maturation in vertebrates [42].…”
Section: Asta and Kiss: A Conserved Neural Circuitry Controlling Matumentioning
confidence: 95%
“…AstA was initially described as an arthropod-specific hormone inhibiting food intake and juvenile hormone (JH) secretion [40]. However, a comprehensive evolutionary study of the AstA receptor 1 gene revealed that it shares an evolutionary ancestor gene with the mammalian GPR54 receptor gene [41]. Moreover, the Drosophila AstA peptide and the human KISS peptide share a conserved FGL motif, suggesting that AstA and KISS could originate from a common ancestor [41].…”
Section: Asta and Kiss: A Conserved Neural Circuitry Controlling Matumentioning
confidence: 99%
“…The C-terminus of allatostatin type A (AST-A) is a conserved FGL amine motif, which can be detected in the brain and midgut of insects; its receptor is a G protein-coupled receptor. AST-A peptide, which can inhibit the secretion of JH, can also regulate food intake through inhibition or reduction of food intake (Felix et al, 2015). After Anopheles mosquitoes sucked blood, the expression levels of AST-A receptor genes GPRALS1 and 2 in the midgut were significantly higher than after the mosquitoes ingested glucose, however, these expression levels were reduced in the head and ovary (Felix et al, 2015).…”
Section: Allatostatinmentioning
confidence: 99%